KARAKTERISTIK PENDERITA KISTA OVARIUM PADA WANITA SEBELUM MENOPAUSE YANG DIRAWAT INAP DI RS. HAJI MEDAN TAHUN 2014-2015 - sri apriani; Hiswani .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Ovarian cyst is one of the gynecological benign tumor most often found in women in their reproductive life. Based on Indonesia Demographic Health Survey incidence of ovarian cysts in Indonesia reached 37,2%. The incidence of ovarian cyst diasease in Sumatera Utara Province is not yet know with certaintybecause the recording and reporting unfavorable. To determine the characteristics of patients with ovarian cyst the women before menopause who are hospitalized at Haji Hospital Medan in 2014-2015 was a descriptive study with case series design. Population and samples of data 126 patients (Total Sampling) with disease proportion 0,66%. Univariate data  were analyzed by descriptive, bivariate data were analyzed with Chi- square. The research found ovarian cysts proportion of patients: age 30-34 years (19,9%), Batak (32,5%), Islam (95,2%), high school education (40,5%), occupation housewife (49,2%), married status (81,0%), the size of the cyst diameter  5,25 – 8,39 cm2 (29,3%), korpus luteum cyst (27,7%), type benign cyst (78,6%),   lower abdominal pain (40,8%), menstrual regularities (87,3%), early menarche (< 12 years) (57,9%), normality (0- 35 u/ml) CA-125 examination yield (61,4%), surgieal treatment (79,4%), the average treatment lenght 7,2 % days or 7 days, the source of the cost of treatment with BPJS/ASKES (83,3%), the origin of the patient was the Medan City (65,9%), out patient home (97,6%), there is no significant difference between the proportion of patients age by menstruation status (p= 0,792), the proportion of patients age by cyst type (p= 0,113), the proportion of cyst type by married status (p=0,774), the proportion of cyst type by the size of the cyst diameter  (p= 0,762), the proportion of menarche story (p=0,470), the proportion of the size of the cyst diameter  by complaints (p= 0,940), the proportion of the average treatment lenght by medical treatment (p=0,237), the proportion of surgieal treatment by state while returning (p = 0,503). Expected to hospital Haji Medan in order to data complementary  be related to with ovarian cyst as parity data. For childbearing age (15-49 age) in order to symptom cyst attention as risk factor happen cyst. Keywords: Ovarian cyst, Characteristics of patients ovarian cyst.